An Exposition of Gandhi’s notion of Satyagraha: A Moral Technique in Conflict Resolution - Dr. Ekta Bhati (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2022)
The present work is an attempt to expound and substantiate Gandhi’s notion of Satyagraha as a moral technique in conflict resolution. The notion of satyagraha efficiently mirrors Gandhi’s dynamic dream of political, social, and individual reconstruction through nonviolent means. Satyagraha with its idealistic intents echoes a holistic vision that aims at the transformation of the adversary to realize both internal and external peace through nonviolent conflict resolution.